Challenges to the Growth of Capital Markets in Under Developed Economies: the Case for Uganda - Sejjaaka, Samuel (TrustAfrica, 2013)
Despite the universal recognition that stock markets are the most pragmatic and cost effective method to raise money for expansion and other projects, companies especially in private sector in underdeveloped economies have consistently shunned this option. As a result, most of the Initial Public Offers (IPOs) and other developments taking place at the capital markets in many developing countries have been state driven, rather than market driven. While private sector firms have shunned the markets, there is evidence that there is demand for share ownership as most of the IPOs done in many of these countries especially in the recent past have been oversubscribed.